Impact of Accounting Conservatism on Improving and Evaluating The efficiency of the financial performance of Islamic banks (An analytical study on Faisal Islamic Bank during 2011 - 2015) - Ahmed, Huda Diayb; Mohammed, Randa Abdelhamied; Yhaya, Badralden Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The importance theory of the research: The research is considered an addition to the Arab library in the field of accounting conservatism. As for the importance of the research from the practical side, the research is additional evidence of the importance of using accounting conservatism in financial statements, especially in debt-intensive institutions such as Islamic banks. Where the research aims to shed light on the relationship of accounting conservatism to improving the efficiency of the financial performance of the bank, comparing these indicators with the criteria of the Basel Committee and the criteria of early warning, and evaluating the financial performance in the level of optimism and pessimism. The research used the descriptive analytical approach of data for the period from (2011-2015) for the financial statements of Faisal Islamic Bank, and to achieve the objectives of the research, finding an important statistical relationship between the level of accounting conservatism and improving and evaluating the efficiency of the financial performance of the bank according to (CAEL) standards (capitaladeguacy capital adequacy, asset quality, ASSETGUALTIY, and profitability EARNINGS, LIGUIDITY). The research reached a set of results, including: that the Faisal Islamic Bank uses accounting conservatism in the published financial statements due to its awareness of the importance of accounting conservatism, and it was found that the use of accounting conservatism in debt-intensive institutions has an impact on improving financial performance Which led to the evaluation of the bank and its classification in the strong degree, i.e. the first degree, and the research recommended a set of recommendations, including: Accounting conservatism should be used in financial institutions with heavy indebtedness because it is important in improving and evaluating the financial performance of the bank, and also has importance in achieving financial indicators such as the indicators of the Committee Basal.